Questioning the Meaning of Financial or State Economic Losses in Corruption Crimes After the Constitutional Court Decision Number 25/PUU-XIV/2016 - Airlangga, Rendy; Abidin, R.B. Muhammad Zainal; Mahendra Suhartono; Purwoleksono, Didik Endro (Faculty of Law, Universitas Pekalongan, 2024)
The Constitutional Court Decision Number 25/PUU-XIV/2016 has changed Articles 2 paragraphs (1) and 3 of the Eradication of Corruption Crime Law from formal criminal act to material criminal act, so that state losses must be interpreted as actual losses. On the basis of that decision, this research analyses the original intent or ratio legis of the word